Implementation of Corporate Social Responsibility in PT PLN Nusantara Power Services in Improving Community Empowerment - Arisandi, Arisandi; Rahayu, Hilda Sri (Universitas Muhammdiyah Yogyakarta, 2025)
This study aims to analyze the implementation of Corporate Social Responsibility carried out by PT PLN (Persero) Distribution of Jakarta Raya and Tangerang in preserving regional culture through regional dance training for elementary school students. The objectives of this study are as follows: How is the implementation of corporate social responsibility in the regional dance program? The method used in this research is qualitative, using a case study approach. Data was obtained using observation, interviews, and documentation studies. Stakeholder theory and the Triple Bottom Line concept are the basis for analysis. The results showed that the implementation of Corporate Social Responsibility by PT PLN (Persero) Jakarta Raya and Tangerang Distribution has involved various stakeholders and had a positive impact on cultural preservation and increased community involvement. The process of implementing Corporate Social Responsibility is well done through planning, implementation, evaluation, and reporting stages. This program not only strengthens the company's relationship with the community but also contributes to the sustainability of local culture. Suggestions given are to increase stakeholder involvement and expand the scope of the program to other schools so that the benefits can be felt more widely.